2019
DOI: 10.3390/met9060653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nb Content on the Mechanical Alloying Behavior and Sintered Microstructure of Mo-Nb-Si-B Alloys

Abstract: Different from conventional Mo-Si-B-based alloys consisting of Moss, Mo 3 Si, and Mo 5 SiB 2 , Mo 3 Si-free Mo-Si-B-based alloys (Moss+Mo 5 Si 3 +Mo 5 SiB 2 or Moss+Mo 5 SiB 2 ) show great potentials for more excellent oxidation resistance and elevated temperature strength. In the present work, alloying element Nb was added to Mo-12Si-10B (at.%)-based alloy to suppress the formation of the Mo 3 Si phase. 20,22,24,26, 28, 30, and 40) bulk alloys were fabricated using mechanical alloying followed by cold pressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The impact of the inclusion of Nb on the characteristics of the Mo-Si-B alloys, therefore, continues to be of importance, and the main concern is to identify the minimum amount of Nb added that can effectively suppress the A15 phase. Based on research, Yang suggested that the optimal range for the critical value of Mo-12Si-10B alloy lies between 24 at.% and 26 at.% [62]. The Mo 3 Si phase was absent in the alloy containing 26 at.% of Nb.…”
Section: Nb Element Modified Mo-si-b Alloysmentioning
confidence: 99%
“…The impact of the inclusion of Nb on the characteristics of the Mo-Si-B alloys, therefore, continues to be of importance, and the main concern is to identify the minimum amount of Nb added that can effectively suppress the A15 phase. Based on research, Yang suggested that the optimal range for the critical value of Mo-12Si-10B alloy lies between 24 at.% and 26 at.% [62]. The Mo 3 Si phase was absent in the alloy containing 26 at.% of Nb.…”
Section: Nb Element Modified Mo-si-b Alloysmentioning
confidence: 99%